2021
DOI: 10.1002/mabi.202000410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anti‐Inflammatory Nanofibers on Urethral Healing

Abstract: Protracted postsurgical inflammation leading to postoperative complications remains a persistent problem in urethral reconstruction. Nanofibers in the form of peptide amphiphiles expressing anti‐inflammatory peptides (AIF‐PA) have positively modulated local inflammatory responses. Urethroplasty is performed to repair 5 mm ventral urethral defects with: uncoated small intestinal submucosa (SIS); SIS dip‐coated with AIF‐PA1 (anti‐inflammatory treatment), or SIS dip‐coated with AIF‐PA6 (control) on 12‐week‐old ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Our study showed that macrophages increased and were predominantly of M1 type in middle-age rat urethra. M1 macrophages are involved in pro-inflammatory responses, and associated with poor urethral injury repair and fibrosis 30 . In addition, mast cells are an unexpected subcluster that appears in the middle-age rat urethra, mast cell-derived histamine and transforming growth factor beta play an important role in inflammation, fibrosis, and smooth muscle cell dysfunction of many tissues 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that macrophages increased and were predominantly of M1 type in middle-age rat urethra. M1 macrophages are involved in pro-inflammatory responses, and associated with poor urethral injury repair and fibrosis 30 . In addition, mast cells are an unexpected subcluster that appears in the middle-age rat urethra, mast cell-derived histamine and transforming growth factor beta play an important role in inflammation, fibrosis, and smooth muscle cell dysfunction of many tissues 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Urethral repair is a complex process involving the proliferation and regeneration of epithelial cells, smooth muscle cells, and endothelial cells, all of which rely on blood vessels to deliver nutrients and oxygen [ 17 , 18 ]. Angiogenesis is an important mechanism for urethral repair, and VECs are the main cells maintaining the physiological functions of blood vessels [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Self-assembling PAs have demonstrated utility in a wide range of settings and applications. [144][145][146][147][148][149][150] PAs are comprised of a hydrophobic alkyl segment attached to a peptide domain that includes a β-sheet forming segment (Figure 4). In aqueous environments, these molecules self-assemble through hydro-phobic collapse of the alkyl domain in combination with hydrogen bonding in the β-sheet domain to produce high aspect-ratio nanofibers.…”
Section: Nanomolecular Treatment Optionsmentioning
confidence: 99%